Simbol-Simbol dalam Buku Kumpulan Puisi Pagar Rumahku Berubah Warna Karya Ama Gaspar: Symbols in the Poetry Collection Pagar Rumahku Berubah Warna by Ama Gaspar - Reni Ambarwati; Wilda Srihastuty Handayani Piliang (ITScience (Information Technology and Science), 2026)
The poetry collection Pagar Rumahku Berubah Warna by Ama Gaspar, particularly the subsection Jendela Olfaktorium, contains various symbols that represent critiques of human suffering. Although the book was nominated for the 2025 Literary Award of the Language Agency, it has not yet been studied through a semiotic approach. This study aims to describe the forms of symbols, interpret their meanings semiotically using the theories of Charles Sanders Peirce and Aminuddin, and examine how these symbols articulate social criticism. This study employed a descriptive qualitative approach. The data consisted of symbolic words, phrases, lines, and stanzas collected from 13 poems in the subsection through reading, note-taking, and documentation techniques. Data analysis was conducted through several stages, including data reduction, data presentation, semiotic interpretation, and conclusion drawing. Data validity was examined through source triangulation, theoretical triangulation, and methodological triangulation through expert discussion. The findings revealed 73 symbolic data, consisting of 22 Blank Symbols, 24 Natural Symbols, and 27 Private Symbols, with Private Symbols being the most dominant category. Through this personal and distinctive sign system, Ama Gaspar goes beyond mere aesthetic expression and transforms her poems into a critical space for examining social realities through a multilayered system of signification. These findings enrich Peircean semiotic studies of contemporary Indonesian poetry and provide an initial reference for further literary research.